1984
DOI: 10.1161/01.str.15.3.458
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic concept of middle cerebral artery occlusion and cerebral infarction in the acute state based on interpreting severe hyperemia as a sign of embolic migration.

Abstract: SUMMARY The present study investigates the pathogenesis of focal cerebral hyperemia, its effect on brain tissue and discusses its pathophysiological and therapeutic importance in the light of interpreting severe hyperemia as a sign of arterial reopening probably due to embolic migration. Cerebral angiography, serial CT-scans and serial TC"-scans were performed in a consecutive group of 73 patients with completed stroke all admitted to hospital within 3 days after stroke onset. When possible the regional cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…In one study using planar ( l33 Xe) imaging focal hyperemias were seen in 8 of 21 patients with MCA occlusion within 4 days of stroke onset. 15 A PET study of 12 patients studied within 48 hours of stroke onset demonstrated that at least some reperfusion had occurred in 4 of 12 patients. 16 A more recent PET study of 18 patients found hyperperfusion in 6 of 18 patients studied between 5 and 18 hours after stroke onset.…”
Section: Discussionmentioning
confidence: 99%
“…In one study using planar ( l33 Xe) imaging focal hyperemias were seen in 8 of 21 patients with MCA occlusion within 4 days of stroke onset. 15 A PET study of 12 patients studied within 48 hours of stroke onset demonstrated that at least some reperfusion had occurred in 4 of 12 patients. 16 A more recent PET study of 18 patients found hyperperfusion in 6 of 18 patients studied between 5 and 18 hours after stroke onset.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16] In contrast to Clarkson et al, we implanted the L-655,708 tablets subcutaneously and used a dosing regimen, following Atack et al, 17 that results in a steady-state plasma drug concentration that is low enough to produce selective α5-subunit-containing GABA A receptor occupancy during the course of treatment. We thereby assessed drug effects following a clinically relevant delivery method at a dose that minimizes side effects by preserving receptor subtype specificity.…”
Section: Introductionmentioning
confidence: 99%
“…These concepts have limited practical application because postischemic CBP, at least in the acute phase, is an unreliable index of tissue viability: it can be extremely low as in "no-reflow" (Ginsberg et aI., 1978;Hossmann, 1982;Kagstrom et aI., 1983) or it can be unneces sarily high in lUXury perfusion when CBP exceeds the metabolic needs of the tissue (Traupe et aI., 1982;Olsen and Lassen, 1984). Therefore, it has increasingly become necessary to characterize isch emic severity and predict tissue survival not only on the basis of perfusion but as a function of changes in basic membrane properties.…”
mentioning
confidence: 99%